MDMA interactions with pharmaceuticals and drugs of abuse. (3rd May 2020) - Papaseit, Esther; Pérez-Mañá, Clara; Torrens, Marta; Farré, Adriana; Poyatos, Lourdes; Hladun, Olga; Sanvisens, Arantza; Muga, Roberto; Farré, Magi
ABSTRACT: Introduction : MDMA (3, 4-methylenedioxymethamphetamine), a synthetic ring-substituted amphetamine, has become one of the most widely used recreational psychostimulant drugs in the world. Among recreational ecstasy/MDMA users, polydrug use is a phenomenon whose common purpose is to experience the synergistic effect of the combined drugs, moderate MDMA effects, prevent potential toxicity, enhance a high or come down from a high from other drugs, or simply to treat existing medical conditions. Thus, MDMA–drug interactions (MDMA-DIs) lead to a higher risk of acute and life-threatening MDMA toxicity. Areas covered : This article provides an overview of the MDMA-DIs with pharmaceuticals and drugs of abuse. In addition, available evidence is summarized along with clinical recommendations. Finally, the increasing importance of MDMA-DIs is highlighted. Expert opinion : There is a reduced number of published MDMA-DIs studies and scarce clinically significant MDMA-DIs documented in the literature. Experimental evidence points out the relevance of MDMA-DI's when MDMA is co-administered with pharmaceuticals that are metabolized by the CYP2D6 due to MDMA inhibitory action and in the case of repeated MDMA administration (MDMA-MDMAIs).